Cholesteatoma in cleft lip and palate: A population based follow-up study of children post ventilation tubes - Spilsbury, Katrina; Ha, J.; Semmens, James; Lannigan, F. (Lippincott Williams and Wilkins, 2013)
Objectives/Hypothesis: To investigate the association of cleft conditions and the development of secondary cholestea-toma following middle ear ventilation tube insertion (MEVTI) in children. Study Design: A retrospective cohort study of all children born after 1980 who underwent at least one MEVTI in a Western Australian hospital from 1980 to 2009 using administrative health data. Methods: The timing and number of MEVTIs, adenoidectomy, type of cleft conditions and cholesteatoma were identified along with demographic variables. Flexible parametric proportional hazards models and hazard functions using age as a time scale were used to estimate the relative rate of developing cholesteatoma.Results: There were 56,949 children who underwent at least one MEVTI during the study period. There were 869 (1.5%) children who also had a diagnosis of a cleft condition. Overall, 594 (1.0%) children developed a secondary cholesteatoma. After taking length of follow-up into account, 6.9% (95% confidence interval [CI], 5.0-9.6) of children with cleft conditions developed cholesteatoma by 18 years of age compared to 1.5% (95% CI, 1.3-1.6) of children without cleft conditions. After adjusting for demographic and clinical variables, children with cleft conditions developed cholesteatoma 7.5 (95% CI, 3.8-18.2) times faster after first MEVTI compared to children without cleft conditions, although by the third MEVTI this difference was no longer statistically significant (P = .257). The rate of developing cholesteatoma in 2005 to 2009 was 0.5 (95% CI, 0.3-0.8) times that of 1980 to 1990. Conclusions: Children with cleft conditions are at increased risk of developing cholesteatoma compared to other children who had one or two MEVTIs, although the overall rate of cholesteatoma is declining.